2009
DOI: 10.1177/1742395309339251
|View full text |Cite
|
Sign up to set email alerts
|

Carers with chronic conditions: changes over time in their physical health

Abstract: This article indicates that there are carers who are themselves suffering from a physical condition or conditions that suggest they are in need of care. Despite these difficulties, these carers are caring for people with quite severe conditions, without any help above that available to other carers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…Family members shared their experience and information, thus providing support to families in similar situations (Magliano et al, 2005;Ware & Raval, 2007). In addition, support from other family members and friends were received frequently in form of a phone call or a visit (Tommis et al, 2009).…”
Section: Chronic Illness Of a Family Membermentioning
confidence: 99%
“…Family members shared their experience and information, thus providing support to families in similar situations (Magliano et al, 2005;Ware & Raval, 2007). In addition, support from other family members and friends were received frequently in form of a phone call or a visit (Tommis et al, 2009).…”
Section: Chronic Illness Of a Family Membermentioning
confidence: 99%
“…19,20 Other studies have identified poor health behaviours among caregivers. 22 The implications for community nursing suggest a need to encompass health-promoting strategies for caregivers when providing care to people with physical disabilities. 21 UK caregivers reported missing meals or hospital treatment because of their caring responsibilities.…”
Section: Caregiver Characteristics Health Problems and Health Behavimentioning
confidence: 99%
“…Higher levels of carer burden are matched by lower self-perceived health status than non-carers and increased prevalence of cognitive impairment [9]. Informal caring can be stressful [3,10,11] and can lead to deterioration in physical and psychological health [12-16]. In the United States, Miller and colleagues have observed that carers “must also cope with their own health problems, typically exacerbated by their caregiving responsibilities” [17].…”
Section: Introductionmentioning
confidence: 99%